2021
DOI: 10.1111/ejn.15424
|View full text |Cite
|
Sign up to set email alerts
|

A novel morphometric signature of brain alterations in type 2 diabetes: Patterns of changed cortical gyrification

Abstract: Type 2 diabetes is a chronic disease that creates atrophic signatures in the brain, including decreases of total and regional volume of grey matter, white matter and cortical thickness. However, there is a lack of studies assessing cortical gyrification in type 2 diabetes. Changes in this emerging feature have been associated mainly with genetic legacy, but environmental factors may also play a role. Here, we investigated alterations of the gyrification index and classical morphometric measures in type 2 diabe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 48 publications
2
13
1
Order By: Relevance
“…The gyrification index and fractal dimension are commonly utilized as key indices of cortical complexity, and aberrations in these parameters may serve as biological markers for neuropsychiatric disorders ( King et al, 2010 ; Matsuda and Ohi, 2018 ), but the conclusions are controversial. Recently research showed individuals with T2DM had higher gyrification index than healthy participants ( Crisóstomo et al, 2021 ), while another study revealed that the gyrification index is lower in T2DM patients with mild cognitive impairment ( Shao et al, 2022 ). Some experts suggest that the relationship between gyrification index and cognitive function is changing dynamically during the progression of neurodegenerative diseases, and also that alterations in various brain areas are not synchronized ( Lebed et al, 2012 ; Núñez et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The gyrification index and fractal dimension are commonly utilized as key indices of cortical complexity, and aberrations in these parameters may serve as biological markers for neuropsychiatric disorders ( King et al, 2010 ; Matsuda and Ohi, 2018 ), but the conclusions are controversial. Recently research showed individuals with T2DM had higher gyrification index than healthy participants ( Crisóstomo et al, 2021 ), while another study revealed that the gyrification index is lower in T2DM patients with mild cognitive impairment ( Shao et al, 2022 ). Some experts suggest that the relationship between gyrification index and cognitive function is changing dynamically during the progression of neurodegenerative diseases, and also that alterations in various brain areas are not synchronized ( Lebed et al, 2012 ; Núñez et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…A 5-year longitudinal study indicated that neurovascular coupling of the insula decreased more severely than in other brain regions in patients with T2DM (Damer and Creutz, 1994 ). A T2DM-associated study showed increased gyrification was found in the temporal lobes, posterior lobe, parietal lobe, and occipital lobe, and decreased gyrification was in the temporal lobe (Crisostomo et al, 2021 ). This study reported clusters different from our study, revealing that other brain regions may be affected by T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Given all of that, GI might offer a more sensitive and objective measurement for studying the cognitive decline in T2DM patients. It is somewhat surprising that only one study, to date, has explored the gyrification changes in patients with T2DM (Crisostomo et al, 2021 ). However, whether and how gyrification is associated with cognition in T2DM patients with MCI remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Participants were selected from the DIAMARKER database 14,15 . Patients were diagnosed in the Endocrinology Department of the Coimbra University Hospital Center using standard World Health Organization criteria 16 and were selected to be part of the follow-up study based on the following criteria: 1) age between 45-75 years old; 2) not having a history of central nervous system disorder, neoplastic, in ammatory, or mental diseases and 3) no history or current alcohol abuse.…”
Section: Participantsmentioning
confidence: 99%